Target-controlled infusion of remimazolam effect-site concentration for total intravenous anesthesia in patients undergoing minimal invasive surgeries - Chon, Jin Young; Seo, Kwon Hui; Lee, Jaesang; Lee, Subin (Frontiers in Medicine, 2024)
Background: Although pharmacokinetic and pharmacodynamic models of remimazolam have been developed, their clinical application remains limited. This study aimed to administer a targetcontrolled infusion (TCI) of remimazolam at the effect-site concentration (Ce) in patients undergoing general anesthesia and to investigate the relationship of the remimazolam Ce with sedative effects and with recovery from general anesthesia.Methods: Fifty patients aged 20-75 years, scheduled for minimally invasive surgery under general anesthesia for less than two hours, were enrolled. Anesthesia was induced and maintained using Schüttler's model for effect-site TCI of remimazolam. During induction, the remimazolam Ce was increased stepwise, and sedation levels were assessed using the Modified Observer's Assessment of Alertness/Sedation (MOAA/S) scale and bispectral index (BIS). Following attainment of MOAA/S scale 1, continuous infusion of remifentanil was commenced, and rocuronium (0.6 mg/kg) was administered for endotracheal intubation. The target Ce of remimazolam and the remifentanil infusion rate were adjusted to maintain a BIS between 40 and 70 and a heart rate within 20% of the baseline value. Approximately five minutes before surgery completion, the target Ce of remimazolam was reduced by 20-30%, and anesthetic infusion ceased at the end of surgery. Nonlinear mixedeffects modeling was employed to develop pharmacodynamic models for each sedation level as well as emergence from anesthesia.The remimazolam Ces associated with 50% probability (Ce50) of reaching MOAA/S scale ≤4, 3, 2, and 1 were 0.302, 0.397, 0.483, and 0.654 µg/mL, respectively. The Ce50 values for recovery of responsiveness (ROR) and endotracheal extubation were 0.368 and 0.345 µg/mL, respectively. The prediction probabilities of Ce and BIS for detecting changes in sedation level were 0.797 and 0.756, respectively. The sedation scale significantly correlated with remimazolam Ce (r = -0.793, P < 0.0001) and BIS (r = 0.914, P < 0.0001). Age significantly correlated with Ce at MOAA/S1 and ROR. Conclusion: Effect-site TCI of remimazolam was successfully performed in patients undergoing general anesthesia. The remimazolam Ce significantly correlated with sedation depth. The Ce50 for MOAA/S scale ≤ 1 and ROR were determined to be 0.654 and 0.368 µg/mL, respectively.